Investigations of thermal plasma with metal impurities. Part І: The influence of electrodes composition on plasma properties - Veklich, A.N.; Lebid, A.V.; Soroka, P.V.; Boretskij, V.F.; Babich, I.L. (Вопросы атомной науки и техники, 2012)
Present paper deals with spectroscopic investigations of electric arc discharge plasma in argon flow between Cu- Mo and Cu-Mo-LaB₆ composite electrodes. Obtained profiles of temperature and electron density were used for calculation of plasma composition and metals’ content in assumption of local thermodynamic equilibrium (LTE). Significant influence of LaB₆ admixture on plasma properties was found.